A comparison of wintering duck numbers among European rice production areas with contrasting flooding regimes. (June 2015) - Pernollet, Claire A.; Guelmami, Anis; Green, Andy J.; Curcó Masip, Antoni; Dies, Bosco; Bogliani, Giuseppe; Tesio, Franco; Brogi, Anne; Gauthier-Clerc, Michel; Guillemain, Matthieu
Highlights: We assessed whether ricefield winter flooding provides suitable habitats to dabbling ducks in Europe. We calculated the mean proportion of winter flooding ricefields in five major duck winter quarters. Mean duck numbers were positively correlated with flooded ricefield area, both through space and time. Flooding ricefields during winter varies considerably between countries owing to differences in policy initiatives. This appears as a valuable habitat management procedure that should get promoted for conservation purposes. Abstract: Agricultural lands can provide suitable habitat for birds under some conditions. In particular, waterfowl sometimes rely on ricefields as nocturnal foraging habitat during winter if post-harvest practices make food accessible. To assess whether the winter flooding of ricefields could be a major driver of duck regional abundance in Europe, we relied on a combination of spatial and temporal analyses. In the former, five of the most important western European rice growing regions in Spain, Italy and France were compared in terms of habitat composition over the 2002–2012 period. The relative importance of natural wetlands and ricefields (either dry or flooded) in determining the abundance of wintering ducks was then established. In the second approach, the trends in duck numbers before and after implementation of winter-flooding Agri-Environment Schemes (AES) were compared in two of the study regions. Both approaches highlighted the role of winter ricefield flooding in explaining wintering duck numbers and complementing the natural wetlands; flooding harvested ricefields improves habitat attractiveness by enhancing food resource accessibility. In Europe, the proportion of ricefields flooded during winter varies considerably between countries (0.17–62%), owing to differences in policy initiatives such as Agri-Environment Schemes. Promoting such schemes more widely across the European rice production area could make a big difference in terms of waterfowl habitat quality at the scale of their wintering range.